The Hikayat Abdullah - Abdullah Abdul Kadir Munshi 1796-1854 (MBRAS reprint, 2009)
For all its shirtcoming - the blunders of fact, the confused chronology and the frequent moral perorations - Munshi Abdullah's autobiography, The Hikayat Abdullah, is a document of much interest to historians of South-East Asia. Munshi Abdullah was an intelligent and articulate man, who had the good fortune to witness at first hand the activities of Stamford Raffles, William Farquhar and other leading personalities both English and Malay. He records in some detail his bird's-eye view of the changes taking place in Malacca and Singapore in the early nineteenth century.